2020
DOI: 10.1016/j.sjbs.2020.06.045
|View full text |Cite
|
Sign up to set email alerts
|

A study on the potential reprotoxic effects of thimerosal in male albino rats

Abstract: Thimerosal is ethyl mercury based compound which is being used as a preservative in vaccines since decades. Pharmaceutical products and vaccines that contain thimerosal are among the potential source of mercury exposure. Current research was intended to ascertain the reprotoxic effects of thimerosal on rat testes. Twenty-four adult male albino rats were sorted into four groups (n = 6). The first group was a control group. Rats of experimental Group 2, 3 and 4 were treated with various dosages of thimerosal (0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 35 publications
(36 reference statements)
1
1
0
Order By: Relevance
“…Capillaries interacted with tubules were dilated and dilation of tubules was also observed in the inner medulla. Animals treated with thimerosal showed damage in tissues in the form of tubular dilation and lesions, which is in line with a previous study conducted on testicular tissues by Ijaz et al (2020). Augmented KIM-1 and NGAL levels also endorse histopathological damages.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Capillaries interacted with tubules were dilated and dilation of tubules was also observed in the inner medulla. Animals treated with thimerosal showed damage in tissues in the form of tubular dilation and lesions, which is in line with a previous study conducted on testicular tissues by Ijaz et al (2020). Augmented KIM-1 and NGAL levels also endorse histopathological damages.…”
Section: Discussionsupporting
confidence: 91%
“…Anti-oxidant enzymes, including CAT, SOD, POD, and GR perform a major role in the intracellular defense against cell damages by free radicals (Lobo et al, 2010). A recent study reported that thimerosal administration led to a dose-dependent reduction in the enzyme activities in rat testes (Ijaz et al, 2020). So, it can be speculated that mercury in the Et-Hg is the primary reason behind the increase in oxidative stress, which led to a decrease in antioxidant enzyme activity and increased lipid peroxidation.…”
Section: Discussionmentioning
confidence: 99%